Barriers to Home Hemodialysis Across Saskatchewan, Canada: A Cross-Sectional Survey of In-Center Dialysis Patients. (August 2020) - Diebel, Lucas; Jafari, Maryam; Shah, Sachin; Day, Christine; McNaught, Connie; Prasad, Bhanu
Background: Despite clinical and lifestyle advantages of home hemodialysis (HHD) compared with in-center hemodialysis (ICHD), it remains underutilized in our province. The aim of the study was to explore the patients' perception and to identify the barriers to use of HHD in Saskatchewan, Canada. Objectives: The primary objective of the study was to evaluate and explore patient perceptions of HHD and to identify the obstacles for adoption of HHD in Saskatchewan. The secondary objective was to examine variations in the patients' perceptions and barriers to HHD by center (main dialysis units vs satellite dialysis units). Design: This is a cross-sectional observational survey study. Setting: Two major centers (Regina and Saskatoon) and 5 associated satellite units attached to each center across the province of Saskatchewan. Patients: We approached all prevalent ICHD patients across Saskatchewan, 398 agreed to participate in the study. Measurements: Self-reported barriers to HHD were assessed using a questionnaire. Methods: A questionnaire was designed to determine the patients' perceived barriers to HHD. Descriptive statistics was used to present the data. Chi-square and Mann-Whitney U test were used to compare the patients' responses between main and satellite units Results: Satisfaction with current dialysis care (91%), increase in utility bills (65%), fear of catastrophic events at home (59%), medicalization of one's home (54%), and knowledge deficits toward treatment modalities (54%) were the main barriers to HHD uptake. Compared with patients dialyzing in our main units, satellite patients chose not to pursue HHD more frequently because they had greater satisfaction with their current dialysis unit care (97% vs 87%, P < .001), felt more comfortable dialyzing under the supervision of medical staff (95% vs 86%, P < .007), could not afford additional utility costs (92% vs 45%, P < .001), were unaware of the risks and benefits of HHD (83% vs 33%, P < .001), had concerns over time commitments for training to HHD (69% vs 32%, P < .001), and had concern for family burnout (60.8% vs 40.6%, P < .001). Limitations: We used questionnaires to quantify known barriers, and this prevents inclusion of additional barriers that individual patients may consider important. Cross-sectional data can only be used as a snapshot. Only 398 patients agreed to participate, and the results cannot be generalized to 740 prevalent HD patients. We did not capture data on demographics (age, income, and literacy level), comorbidities, and dialysis vintage, which would have been helpful in interpretation of the results. Conclusions: Satisfaction with in-center care, lack of awareness and education, specifically in the satellite population, concerns with family burnout, expenses associated with utilities, and training time will need to be addressed to increase the uptake of HHD. Trial Registration: The study was not registered on a publicly accessible registry as it did not involve any health care intervention on human participants.